Acute abdominal pain in triage: A retrospective observational study of the Manchester triage system's validity. Issue 7 (25th January 2021) - Zaboli, Arian; Ausserhofer, Dietmar; Pfeifer, Norbert; Magnarelli, Gabriele; Ciccariello, Laura; Siller, Marianne; Turcato, Gianni
Abstract: Objective: Roughly 5% to 10% of patients admitted to the emergency department suffer from acute abdominal pain. Triage plays a key role in patient stratification, identifying patients who need prompt treatment versus those who can safely wait. In this regard, the aim of this study was to estimate the performance of the Manchester Triage System in classifying patients with acute abdominal pain. Methods: A total of 9, 851 patients admitted at the Emergency Department of the Merano Hospital with acute abdominal pain were retrospectively enrolled between 1 January 2017 and 30 June 2019. The study was conducted and reported according to the STROBE statement. The sensitivity and specificity of the Manchester Triage System were estimated by verifying the triage classification received by the patients and their survival at seven days or the need for acute surgery within 72 h after emergency department access. Results: Among the patients with acute abdominal pain (median age 50 years), 0.4% died within seven days and 8.9% required surgery within 72 hours. The sensitivity was 44.7% (29.9–61.5), specificity was 95.4% (94.9–95.8), and negative predictive value was 99.7% (99.2–100) in relation to death at seven days. Conclusions: The Manchester Triage System shows good specificity and negative predictive value. However, its sensitivity was low due to the amount of incorrect triage prediction in patients with high‐priority codes (red/orange), suggesting overtriage in relation to seven‐day mortality. This may be a protective measure for the patient. In contrast, the need for acute surgery within 72 h was affected by under‐triage. Relevance to clinical practice: The triage nurse using Manchester Triage System can correctly prioritise the majority of patients with acute abdominal pain, especially in low acuity patients. The Manchester Triage System is safe and does not underestimate the severity of the patients.